Impact of the COVID-19 pandemic on patients diagnosed with Fibromyalgia at the Rheumatology outpatient clinics in Aracaju, SE (Research, Society and Development, 2023)
The new COVID-19, first reported in China in December 2019, was declared a public health emergency of international concern in January 2020 by the World Health Organization (WHO). The consequences of this pandemic have had a significant impact on individuals' daily routines, negatively affecting patients with chronic pain. Fibromyalgia (FM) is a chronic condition characterized by widespread pain, fatigue, sleep disturbances, and cognitive changes. Its prevalence is estimated at 2.5% in Brazil, being more common in women. Demographic, socioeconomic, and psychosocial factors have been associated with greater pain intensity and interference during social distancing in these patients. This impact is related to the closure of clinics and physical activity spaces, healthcare professionals being diverted to COVID related activities, increasing wait times for consultations, delays in timely access to medications due to reduced prescription, reduced visits to physiotherapists, psychologists, and self-help groups, and the closure of group activity programs such as gyms, which previously facilitated social interaction, contributing to decrease quality of life (QL). The objective of this study was to evaluate the impact of these factors on the QL and pain of fibromyalgia patients during a pandemic. To this end, patients with fibromyalgia from three clinics in Aracaju-SE were interviewed using questionnaires. The data from this study suggest an association between pandemic lockdown and worsening symptoms, as well as the QL of patients living with this disease, especially when evaluated pain, mood, and sleep. Treatment interruption during this period and the presence of other associated comorbidities worsened the health condition.